Wheeled Robot with Ardublock Programming for Elementary School Students - F E Purnomo; M A Firmansyah (Fakultas Teknik Universitas Bhayangkara, 2021)
Robotics technology can be implemented into the elementary school curriculum with the presence of extracurricular robotics or better as robotics only. Robotics in students is taught to assemble and program simple robots packaged in robotics learning media. Robotics activities basically use wheelled robots but have different functions. With the basic assumption of the robot, we can reduce the cost of procurement by making a robot with one wheel but with various functions. The wheeled robot is portable, so it is easy to disassemble. Robotics activities in generaly uses an Arduino controller with the C programming language. Elementary school students have difficulty understanding the language. Ardublock as one of the easy and open-source solutions. This research focused on the working system of a wheeled robot with various features (line tracer, transporter, and wall tracking) as well as the success in using ardublock logic as the programming language of the robot. The results test show that the ardublock program can be used to program the Arduino controller on the robot. The wheeled robot with the line follower feature recorded a travel time of 6.0 seconds on a 200cm trajectory. The wheeled robot with a transporter feature on a 200 cm trajectory takes an average of 8.9 seconds with the success of lifting objects 7 times out of 10 attempts.